Computerized adaptive testing: a general perspective - Barrada, Juan Ramón (Anales de Psicología / Annals of Psychology, 2012)
Computerized adaptive testing (CAT) adapts the items to be administered to each examinee according to the responses to the previous items. In this way, more accurate trail level estimations can be obtained or test length is reduced. In the last years, several CATs have been developed in Spain and it can be expected that, given the advantages of this tech- nique, more will become available soon. The goal of this work is to offer and updated view of this topic. For doing so, the basic structure of a CAT is presented and the different steps composing it are commented. Special emphasis is given ot item selection, the fundamental part for the adaptability of the test, from the perspective of the four objectives that must be satisfied by a CAT: (a) accuracy, (b) item bank security; (c) content bal- ance; and (d) test maintenance.